Development of an occupational profile for proper location of the young with mental retardation in an occupational workshop - Sotil Brioso, Amparo (1998)
The research establishes the occupational profiles of the student with mental retardation considering their real potentialities; abilities, skills and aptitudes, contributing in that way to an adequate allocation in a Occupational Workshop improving their preparation, and by this way making possible their inclusion in the labor world.